Panorama 5 : jamais vu - Alphant, Marianne; Crinière, Nathalie; Panorama Le Fresnoy, Tourcoing 2004 (Tourcoing : Le Fresnoy, 2004)
Alvarado, Marta ; Bernard, Thierry ; Bosson, Olivier ; Bourgeois, Blaise ; Braila, Pavel ; Cera, Andrea ; Chatonsky, Grégory ; Coïc, Julien ; Cury, Flavio ; Dauchez, Cécile ; Devos, Nicolas ; Dimnet, Morgan ; et al.
Fresnoy, Studio national des arts contemporains, du 11 juin au 6 juillet 2004
kunstcatalogus